Application of solar thermal collectors for energy consumption in public buildings – An updated technical review - Omeiza, Lukman Ahmed; Abid, Muhammad; Dhanasekaran, Anitha; Subramanian, Yathavan; Raj, Veena; Kozak, Kateryna; Mamudu, Ukashat; Azad, Abul Kalam (Maǧallaẗ al-abḥath al-handasiyyaẗ, 2024)
The daily energy demand in public buildings has been on the rise, partly due to the intensive use of building energy-comfort technologies. Hot water production, space heating and air-conditioning are the major consumers of energy in public buildings; if their energy demand can be addressed holistically through the integration of solar collectors with public buildings, it will bring about a reduction in energy costs. Fossil fuels, such as coal, oil and gas, are the most significant contributor to global climate change, accounting for over 75% of global greenhouse gas emissions and nearly 90% of all carbon dioxide emissions. Environmental experts are clear, that to avoid the worst impacts of climate change, emissions need to be reduced by almost half by 2030 and reach net-zero by 2050. To meet the global energy demand and minimise environmental hazards, the world needs to reduce its over-reliance on fossil fuels for public building energy consumption and invest in alternative sources of energy that are clean, accessible, affordable, sustainable, and reliable. Our review aims to provide a comprehensive analysis on the various uses of solar thermal collectors in public buildings as a source of green energy supply. The benefits of a potential developed nano-coated absorber surface for solar collectors were studied, and its possible effect on minimising corrosion in heat pipes, absorber surfaces and thermal storage tanks was considered. The merits of using solar collectors, as well as the knowledge gap, limitations, trends and future research prospects are discussed elaborately. Critical attention was paid to recent and past developments in this regard, a technical outlook of various studies is highlighted, and the link between them in addressing the world's over-dependence on fossil fuels is studied.